2015
DOI: 10.5901/mjss.2015.v6n3s1p246
|View full text |Cite
|
Sign up to set email alerts
|

Social Media for Collaborative Learning and Engagement: Adoption Framework in Higher Education Institutions in Malaysia

Abstract: This paper addresses collaborative learning and engagement via intention towards

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 27 publications
9
32
1
Order By: Relevance
“…The participants also indicated that they would use social media to improve their research skills and to build relationships with their supervisors thus further improving their academic performance while facilitating academic activities and cooperating with other researchers. As a result of these findings, hypotheses H3b, H3c, H4a, H4b and H5 are confirmed, which agrees with the results of several past studies (Ainin et al, 2015;Alrahmi et al, 2015a;Al-rahmi et al, 2014;Alloway and Alloway, 2012;Al-rahmi et al, 2015b;Al-rahmi et al, 2015c) but contradicts the findings of past studies that suggested that the frequent use of social media harms academic performance (Kirschner et al, 2010).…”
Section: Figure 2 Results For Proposed Frameworksupporting
confidence: 84%
See 1 more Smart Citation
“…The participants also indicated that they would use social media to improve their research skills and to build relationships with their supervisors thus further improving their academic performance while facilitating academic activities and cooperating with other researchers. As a result of these findings, hypotheses H3b, H3c, H4a, H4b and H5 are confirmed, which agrees with the results of several past studies (Ainin et al, 2015;Alrahmi et al, 2015a;Al-rahmi et al, 2014;Alloway and Alloway, 2012;Al-rahmi et al, 2015b;Al-rahmi et al, 2015c) but contradicts the findings of past studies that suggested that the frequent use of social media harms academic performance (Kirschner et al, 2010).…”
Section: Figure 2 Results For Proposed Frameworksupporting
confidence: 84%
“…In one study, Churchill (2009) demonstrated that blogs used for educational and social issues promoted a beneficial learning setting. In general, social media is seen to deliver benefits including increased social interactions through the use of e-media, access to information, increased creativity, the creation of a sense of belonging, the promotion of engagement and collaborative learning, the minimizing of barriers such as distance and socio-economic status in a group resulting in more interactions and communication between members, and improving the technological skills of users (Al-rahmi et al, 2015b;Zwart et al, 2011;Connolly, 2011;Hendrickson et al, 2011). Yet other studies have indicated that the use of Facebook is seen as an appropriate tool for interactions between teacher and students (Baran, 2010).…”
Section: Social Media and Students' Academic Performancementioning
confidence: 99%
“…Thus, "this research defines resource sharing as the degree where a student's beliefs that resource sharing would enrich their teaching and learning". These results are consistent with [24,25], who argued that resource sharing with peers was useful on educational use. See Table 1.…”
Section: A Descriptive and Examination Of Factorssupporting
confidence: 92%
“…Thus, "this research defines perceived usefulness at a degree where a student's beliefs perceived usefulness on social media use would enrich their teaching and learning". These results are consistent with [25,29,35,36,37,38], who argued that perceived usefulness on social media use was useful on teaching and learning. See Table 6.…”
Section: A Descriptive and Examination Of Factorssupporting
confidence: 90%
See 1 more Smart Citation